The hope for success and the sense of happiness in men dealing with the divorce crisis - Anna Małgorzata Dudak (Jesuit University Ignatianum in Krakow, 2019)
RESEARCH OBJECTIVE: The aim of the research conducted among men dealing with the divorce crisis was to examine the correlation between the fathers' hope for success, understood as their confidence in the willpower and competence to overcome difficult situations, and their sense of happiness. THE RESEARCH PROBLEM AND METHODS: The main aim of the research was to address the question of whether there exists a correlation between the hope for success and the sense of happiness in fathers dealing with the divorce crisis and, if so, what is the nature of this connection. The study employed Hope for Success Questionnaire (the Polish adaptation of C. Snyder's Hope Scale). The level of happiness was determined with the use of the Oxford Happiness Questionnaire. THE PROCESS OF ARGUMENTATION: The disquisition consists of five parts. First, the author introduces the problem and discusses the situation of contemporary fathers dealing with the divorce conflict. The second part outlines the assumptions of the research. Then, the article offers the theoretical framework regarding the hope for success and the sense of happiness. This part is followed by the analysis of the research material. The final part contains a conclusion. RESEARCH RESULTS: The results revealed significant interdependence between the general level of hope for success and willpower, and the sense of happiness of the fathers participating in the study. The analysis of the material concerning the differences in the level of hope for success and the sense of happiness that took into account socio-demographic profile of the respondents displayed statistically significant differences as far as the financial situation of the fathers is concerned. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: It may be assumed that in the case of fathers interested in the improvement of their relationship with the child after the divorce, the hope for success and conviction about their effectiveness and persistence foster their mental well-being, encourage the adoption of a more optimistic approach, and help find self-acceptance.